Exploring the motivations of pregnant women to seek health information: A qualitative study - Marzieh Javanmardi; Mahnaz Noroozi; Firouzeh Mostafavi; Hasan Ashrafi-Rizi (Wolters Kluwer Medknow Publications, 2022)
Background: Health information-seeking behavior is directed by various factors. Understanding the motivations of pregnant women to obtain health information can facilitate evidence-based policy-making to enhance their health literacy. Therefore, this study was conducted to explore the motivations of pregnant women to seek health information. Materials and Methods: In this qualitative study with a content analysis approach, 39 participants, including pregnant women, midwives, and gynecologists in Isfahan city, Iran, were selected via purposive sampling with maximum variation strategy. Individual interviews, field notes, and daily notes were used to collect data, which was then analyzed using conventional qualitative content analysis. Results: Analysis of data resulted in one main category of "strive to protect the health of mother and fetus." This main category consisted of four subcategories, including "increasing information related to maternal and fetal health," "preventing recurring problems or causing complications in pregnancy," "reducing worry about pregnancy problem," and "receiving encouragement from the spouse, relatives, and healthcare providers." Conclusions: According to the findings, pregnant women seek health information for a variety of reasons, including learning more about their own health and that of their fetus, preventing recurring problems or complications, alleviating concerns about pregnancy problems, and receiving encouragement from husbands, relatives, and healthcare providers. Thus, health professionals, midwives, and antenatal care providers should be aware of these issues and provide more evidence-based information to pregnant women at the time they require it.